RhD alloimmunization – diagnostics, therapy and prophylaxis - Ciesielski, Radoslaw; Mich, Anna; Perkowska, Klaudia; Kaźmierczak, Anna; Izdebska, Wiktoria; Sornek, Patrycja; Borkowska, Agata; Kiełb, Anna; Pawlak, Igor; Stanek, Jakub (Quality in Sport, 2024)
Introduction: The success in preventing and treating Rh D alloimmunization is a major accomplishment in modern obstetrics. The widespread use of Rh D immune globulin has led to a decline in red cell alloimmunization. Despite evidence of its effectiveness, many cases of Rh D alloimmunization persist due to non-compliance with established protocols. Implementing routine anti-D prophylaxis (RAADP) during the third trimester is well-established but requires more careful. Aim of study: The aim of the study is to summarize the available knowledge about alloimmunization in pregnancy and methods of prophylaxis. The definition, patomechanism, methods of treatment and prophylaxis were summarized and described. Materials and methods: The literature available in PubMed database was reviewed using following keywords: “alloimmunization in pregnancy”, “serological conflict”, “fetal anemia”, “HDFN”, “prophylaxis of alloimmunization”. Conclusion: Advancements in diagnosing, treating, and preventing hemolytic disease of the fetus and newborn are notable. Quick, non-invasive diagnostics have facilitated more efficient treatment implementation. Prevention methods include specific and nonspecific prophylaxis, which can start during or after pregnancy. Numerous guidelines and studies exist regarding immunoglobulin use in pregnancy. However, medical staff education on managing hemolytic disease during pregnancy is crucial.